Financial Management Application Development in Cargo Companies Using Agile Approach - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
Effective financial management is crucial for cargo companies to maintain operational continuity and improve business efficiency. However, many cargo companies need help managing their finances effectively, especially related to the complexity of operations and high volume of transactions. This research aims to develop a cargo financial management application using an Agile approach to overcome these problems. The research method includes requirements definition, planning, development, and testing stages. Cargo companies' needs for financial management applications were identified through a series of stakeholder interviews and business process analysis. Next, a project plan is drawn up, a development team is determined, and potential risks are identified to direct the application development process. In the development phase, the system design of the application is conceived, core features are developed using Agile methodology, and integration with other systems in the company is performed. Testing was conducted to ensure optimal application functionality and performance. The result is a financial management application that is adaptive, responsive, and can improve the efficiency of financial management and cargo company operations. The contribution of this research is to provide an effective solution to overcome the challenges in the financial management of cargo companies and provide a foundation for the development of similar applications in the context of other cargo industries.